Ahkam Az-Zawaj; Hukum-Hukum Perkawinan: Kitab Fathul Mu’in Bi Syarhi Qurratil ‘Ain Bi Muhimmatiddin - Faishal Faishal; Mhd. Amar Adly; Heri Firmansyah (Student Research Journal, 2025)
This study aims to examine the laws of marriage as outlined in the Fathul Mu’in Bi Syarhi Qurratil ‘Ain Bi Muhimmatiddin manuscript through an analysis of Islamic jurisprudential sources and principles. The research employs a qualitative method based on a literature study with a descriptive-analytical approach. The focus includes explanations of marriage laws under various circumstances, encompassing obligatory, recommended, disliked, prohibited, and permissible rulings, aligned with Islamic jurisprudential principles and individual contexts. The findings reveal that marriage laws in Islam are flexible and adaptable, depending on the illah (legal reasoning) or conditions of individuals, as elaborated in the referenced text and supported by the Qur'an and Hadith. The research addresses the issues of how Islamic marriage laws are applied and how this text contributes to both theoretical and practical understandings of marriage jurisprudence.